Self-management in the city: the experience of the Asociación de Pobladores from «El Brillante» sector - Alvarado Castro, Huber (2019)
The Association of Settlers of the Brillante sector is one of the experiences of the Urban Self-Management Community of Lima and of the less studied places such as the social case, at that moment the reflection on the management of the neighborhood organization and the changes that faced an agreement its local community, for from this, the effects of the government and the changes in its organic structure and the insertion of new members of the association’s board.